Middle School: Escape to Australia - Book 9 - Patterson, James 1947-; Chatterton, Martin; Griffo, Daniel (New York ; JIMMY Patterson Books, Little, Brown and Company, 2017)
The trip to Australia Rafe has won starts badly, but after connecting with a group of misfits he finds a way to do what he does best--create mayhem.
Accelerated Reader AR
Keywords: JUVENILE FICTION / Humorous Stories; JUVENILE FICTION / People & Places / Australia & Oceania; JUVENILE FICTION / Social Issues / Adolescence; JUVENILE FICTION / Social Issues / New Experience; JUVENILE FICTION / Family / Alternative Family